LİMBERG FLEBİN ÇOK AMAÇLI UYGULAMALARI - PEKER, Fatih; SOLAKOĞLU, Can (Cerrahpaşa Medical Journal, 2014)
Background.- When skin grafting is not desirable, the Limberg flap is a useful method in closing large defects, which can not be closed primarily. While a single Limberg flap is frequently used at the face to close moderate defects, multi-Limberg flap techniques can help to cover moderate to large defects at the other body are as. In thirty-eight cases (mean age 55 years-old, 26 male, 12 female), single or multi-Limberg flaps were used to reconstruct skin defects at the lower extremities and the face. Vast majority of the lesions were in facial region and varied 2-10 cm² in size. Thirty Limberg flaps were designed around malignant lesions. Results.- Mean follow-up period was 14 months. We did not observe any major complications related to surgery. Acceptable aesthetic and functional results were achieved in all of the patients. Conclusion.- The versatility and plasticity of Limberg flaps allow the reconstruction of many defects in different localizations and orientations of the body and especially all over the face including cheek, paranasal, buccomandibular and periorbital areas.